Cooperation between Ukraine and countries of the Visegrad Group in the format V4+1 - Мудрієвська, І. (Київський національний університет імені Тараса Шевченка, 2013)
The author analyzed basic directions of cooperation of Ukraine with the countries of the Visegrad Group in the format V4 +1 in the context of european integration strategy, reported the achievements and prospects of further cooperation.

Розкрито основні напрями співробітництва України з державами Вишеградської групи у форматі В4+1 в контексті євроінтеграційної стратегії, висвітлені здобутки та перспективи подальшої взаємодії.
Співробітництво України і держав Вишеградської групи у форматі в 4+1
Keywords: Ukraine; Visegrad Group; european integration; Україна; Вишеградська група; євроінтеграція